2017
DOI: 10.1111/jnc.14250
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione reductase mediates drug resistance in glioblastoma cells by regulating redox homeostasis

Abstract: Glutathione (GSH) and GSH-related enzymes constitute the most important defense system that protects cells from free radical, radiotherapy, and chemotherapy attacks. In this study, we aim to explore the potential role and regulatory mechanism of the GSH redox cycle in drug resistance in glioblastoma multiforme (GBM) cells. We found that temozolomide (TMZ)-resistant glioma cells displayed lower levels of endogenous reactive oxygen species and higher levels of total antioxidant capacity and GSH than sensitive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 44 publications
6
94
2
Order By: Relevance
“…Similar results were reported in clear cell renal carcinoma, where silencing the GSH biosynthesis pathway was shown to trigger ferroptosis (47). Thus, modulation of redox homeostasis by GSH/GSR appears to be an important key modulating sensitivity of cancer cells to chemotherapy (46). Interestingly, in our study, decreased levels of glutathione metabolism-related genes GSS, GSR, GPX2, IDH were observed in cells in which FZD7 was knocked down and increased expression of this signature was recorded in cells overexpressing the receptor.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results were reported in clear cell renal carcinoma, where silencing the GSH biosynthesis pathway was shown to trigger ferroptosis (47). Thus, modulation of redox homeostasis by GSH/GSR appears to be an important key modulating sensitivity of cancer cells to chemotherapy (46). Interestingly, in our study, decreased levels of glutathione metabolism-related genes GSS, GSR, GPX2, IDH were observed in cells in which FZD7 was knocked down and increased expression of this signature was recorded in cells overexpressing the receptor.…”
Section: Discussionsupporting
confidence: 79%
“…Lower levels of endogenous ROS and higher levels antioxidants and GSH were found in temozolomide (TMZ)-resistant glioblastoma cells. The expression of GSR was also higher in TMZ-resistant compared to sensitive cells and silencing GSR in drug-resistant cells improved sensitivity to TMZ or cisplatin (46). Similar results were reported in clear cell renal carcinoma, where silencing the GSH biosynthesis pathway was shown to trigger ferroptosis (47).…”
Section: Discussionsupporting
confidence: 77%
“…Also, the treatment with NMDA along with H 2 O 2 resulted in a significant decrease in the ROS levels of cells, compared with cells exposed to H 2 O 2 alone, in both the cell lines (Figures D and E) indicating the significance or NMDAR in mitigating the ROS in presence of exogenous oxidative stress. Zhu et al () have reported that LN18 and T98G glioma cells expressed high levels of GR, whereas, LN229 and U251MG glioma cells expressed low levels of GR. Therefore, as evidenced by different studies, it can be appreciated that cell‐specific redox balance might differ due to various intrinsic factors; these effects may be attributed as an explanation for observed difference in the ROS level in two cell types used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells, in addition to producing high levels of ROS, are also likely to be exposed to further oxidative stress by exogenous ROS‐generating agents (Zhu et al, ). In U87MG glioma cells, a 2 h exposure to temozolomide, a DNA alkylating antineoplastic drug resulted in a twofold increase in ROS production (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation